2016
DOI: 10.1186/s12944-016-0368-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intensive insulin treatment on plasma levels of lipoprotein-associated phospholipase A2 and secretory phospholipase A2 in patients with newly diagnosed type 2 diabetes

Abstract: BackgroundChina has the highest absolute disease burden of diabetes worldwide. For diabetic patients, diabetes-related vascular complications are major causes of morbidity and mortality. The roles of lipoprotein-associated phospholipase A2 (Lp-PLA2) and secretory phospholipase A2 (sPLA2) as inflammatory markers have been recently evaluated in the pathogenesis of both diabetes and atherosclerosis. We aimed to determine the mechanism through which patients with newly diagnosed type 2 diabetes gain long-term vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Cytosolic PLA 2 (cPLA 2 ) exhibits preference for hydrolysis of ARA from phospholipid substrates, and expression is induced through a number of signaling pathways activated by acute exercise including MAPK/ERK (mitogen-activated protein kinases/ extracellular signal-regulated kinases), and transcriptional activators such as nuclear factor-kappa B (NF-κB) and proinflammatory cytokines [ 35 , 36 ]. Post-exercise plasma ARA levels were significantly reduced with carbohydrate intake, and these data imply that PLA 2 activity was attenuated, perhaps in part due to higher glucose and insulin levels as extrapolated from diabetes-based investigations [ 26 , 37 ]. In a previous study conducted by our research group utilizing the same exercise model, we showed that serum insulin levels increased 29% after 75-km cycling with carbohydrate compared to a decrease of 28% with water only [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytosolic PLA 2 (cPLA 2 ) exhibits preference for hydrolysis of ARA from phospholipid substrates, and expression is induced through a number of signaling pathways activated by acute exercise including MAPK/ERK (mitogen-activated protein kinases/ extracellular signal-regulated kinases), and transcriptional activators such as nuclear factor-kappa B (NF-κB) and proinflammatory cytokines [ 35 , 36 ]. Post-exercise plasma ARA levels were significantly reduced with carbohydrate intake, and these data imply that PLA 2 activity was attenuated, perhaps in part due to higher glucose and insulin levels as extrapolated from diabetes-based investigations [ 26 , 37 ]. In a previous study conducted by our research group utilizing the same exercise model, we showed that serum insulin levels increased 29% after 75-km cycling with carbohydrate compared to a decrease of 28% with water only [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We sought to determine if carbohydrate intake during exercise countered other PUFA-derived oxylipins, a likely finding given their important immune and inflammation regulatory roles. One potential mechanism for the influence of carbohydrate intake on lipid-related metabolites during exercise is the associated increase in insulin that inhibits tissue triacylglycerol lipase, hormone sensitive lipase, and PLA 2 , thus reducing triacylglycerol breakdown and the release of free fatty acids into circulation [ 26 , 27 ]. Prolonged exercise increases PLA 2 activity in muscle tissue, and the potential countermeasure influence of acute carbohydrate ingestion through related increases in insulin and other factors should result in a reduced release of oxylipins and inflammatory lipid mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Lp‐PLA2 activity significantly rose in patients of type 2 diabetes during the early stages of the disease. T2DM patients in whom Lp‐PLA2 activity was elevated were also more likely to develop CAD than those without elevated levels . Therefore, it is indicated that AAP tend to produce high CVD risk in the early stages of treatment and before hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, positive correlations between Lp‐PLA2 and several atherogenic factors in patients with newly diagnosed diabetes as well as the cardio‐ankle vascular index, a recently developed marker of arterial stiffness, in long‐term T2DM patients were demonstrated recently . Lin et al proposed that Lp‐PLA2 might affect the incidence of atherosclerosis in diabetic patients and the decline in Lp‐PLA2 levels through intensive insulin therapy might contribute to protection from diabetic atherosclerotic complications . Additional studies are essential to clarify the role of Lp‐PLA2 in modifying the atherosclerotic process of T2DM patients.…”
Section: Biological Functions and Disease Implicationsmentioning
confidence: 99%